Detection of the adsorption of water monolayers through the ion oscillation frequency in the magnesium oxide lattice by means of low energy electron diffraction - Guevara Bertsch, Milena (2016)
We investigate the variation of the oscillation frequency of the Mg2+ and O2− ions in the magnesium oxide lattice due to the interactions of the surface with water monolayers by means of Low Energy Electron Diffraction. Our key result is a new technique to determine the adsorbate vibrations produced by the water monolayers on the surface lattice as a consequence of their change in the surface Debye temperature and its chemical shift. The latter was systematically investigated for different annealing times and for a constant external thermal perturbation in the range of 110–300 K in order to accomplish adsorption or desorption of water monolayers in the surface lattice.